ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK BUMI DAN BANGUNAN PEDESAAN DAN PERKOTAAN (PBB-P2) TERHADAP PENDAPATAN ASLI DAERAH KOTA TANGERANG 2014-2018 - Nurlaelah Nurlaelah; RR. Prima Dita Hapsari (Sekolah Tinggi Ilmu Ekonomi La Tansa Mashiro, 2022)
In accordance with Law no. 28 of 2009 Land and Building Tax has become a local tax. Regional Original Income (PAD) will increase because new types of local taxes have been added. This study aims to determine the effectiveness and contribution of Rural and Urban Land and Building Tax revenue (PBB-P2) to Regional Original Income (PAD). The method used in this study is a quantitative research method and the data used in this study is secondary data, obtained from the Regional Revenue Agency (BPD) Tangerang City.The results of this study indicate that Land and Building Tax receipts from 2014-2020 fluctuate every year, not always increasing or decreasing. Contribution to Regional Income tends to increase